Enterprise information systems and advancing business solutions : emerging models - Tavana, Madjid, 1957- (Business Science Reference, 2012)
"This book is to provide comprehensive coverage and understanding of various enterprise information systems (EIS) such as enterprise resource planning (ERP) and electronic commerce (EC) and their implications on supply chain management and organizational competitiveness"--Provided by publisher.